Cost burden of malaria: evidence from Nigeria (2016)
This paper provides findings on cost burden of malaria in Nigeria. Cost computations were extrapolated to monthly income fraction and GDP lost to the illness. Results of the study are shown across different employment groups. Computations for indirect and direct costs were conducted using the Human capital and Bottom up approach respectively. The results show that one in two persons employed in the labour force will experience loss in labour contribution as a result of malaria with indirect cost of about N5,532.59($37.16) and N4,828.73 ($32.43) per person per day for the patient and care giver, respectively. Individuals spend approximately N2,730.46($18.34) on the average for treatment of one bout of the illness which translates to approximately 3% of monthly income. Overall, indirect and direct costs related to one episode of malaria in Nigeria sum up to approximately N1, 906.08 billion ($12,801.07 million) implying about 8% of GDP. GDP fraction lost to malaria is higher for the informal sector particularly self-employment in agriculture. Strategies to enhance welfare, labour contributions and economic output in Nigeria should focus on adequate measures to reduce malaria prevalence or complete eradication.